2020
DOI: 10.1186/s13046-020-01567-1
|View full text |Cite|
|
Sign up to set email alerts
|

Long non-coding RNA NCK1-AS1 promotes the tumorigenesis of glioma through sponging microRNA-138-2-3p and activating the TRIM24/Wnt/β-catenin axis

Abstract: Background: Glioma is a common brain malignancy with high mortality. The competing endogenous RNA (ceRNA) networks may play key roles in cancer progression. This study was conducted to probe the role of long noncoding RNA (lncRNA) NCK1-AS1 in glioma progression and the involved mechanisms.Methods: Microarray analyses were performed to explore the lncRNAs/miRNAs/genes with differential expression in glioma. NCK1-AS1 levels in glioma tissues and normal brain tissues, and in glioma cell lines and normal human gli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…For example, lncRNA NCK1-AS1 enhances growth and metastasis of glioma through targeting miR-138-2-3p to activate βcatenin signaling. 2 LncRNA CCAT2 contributes to glioma progression by activating VEGFA pathway. 15 LncRNA LINC00467 upregulation promotes glioma development through repressing P53 level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, lncRNA NCK1-AS1 enhances growth and metastasis of glioma through targeting miR-138-2-3p to activate βcatenin signaling. 2 LncRNA CCAT2 contributes to glioma progression by activating VEGFA pathway. 15 LncRNA LINC00467 upregulation promotes glioma development through repressing P53 level.…”
Section: Discussionmentioning
confidence: 99%
“…1 The current clinically therapeutic strategies are surgery combined with chemotherapy and radiotherapy. 2 However, the prognosis of glioma patients remains not well post therapy. 3 Hence, it is urgently required to discover new molecular mechanism for glioma therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The siRNA-mediated Bcl-xL downregulation potentiates the inhibitory effect on the malignancy and growth of PCa cells [ 78 ]. Another example of successful siRNA treatment is the tripartite motif-containing protein 24 (TRIM24), a carcinogenesis factor capable of enhancing progression and viability of different cancers [ 79 , 80 ]. The strategy is based on suppressing TRIM24 in cancer therapy [ 81 ].…”
Section: Sirna Targets Signaling Pathways: Focus On Pca Therapymentioning
confidence: 99%
“…NCK1-AS1 was found to serve as oncogenic lncRNA in several cancers. 9,10,17 However, the roles and associated mechanisms of NCK1-AS1 in regulating GC remain unclear. In this study, we showed that NCK1-AS1 was upregulated expression in GC tissues and cells, indicating that NCK1-AS1 may play a crucial role in regulating GC progression.…”
Section: Dovepressmentioning
confidence: 99%